1991
DOI: 10.1002/cjce.5450690515
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of spent activated carbon by wet air oxidation

Abstract: The regeneration of activated carbon was studied using the wet air oxidation process in the temperature range of 150-240°C and oxygen partial pressure range of 0.2 to 1 .O MPa. Phenol was used as substrate. The overall mechanism of regeneration has been analysed and the different steps taking place during the regeneration process were individually investigated. Kinetics of oxidation of phenol and oxygen mass transfer coefficients have been estimated in the ranges of temperature and pressure studied. Oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 12 publications
5
44
0
Order By: Relevance
“…18 Simultaneously, WAO has been extensively studied for the regeneration of AC spent with organic compounds after its use in adsorption processes. 19,20 Also, AC and other carbonaceous materials have been successfully tested as supports for catalysts, 21 even for CWAO of low molecular weight acids. 21±24 Recently, a study carried out in a trickle bed reactor has demonstrated that activated carbon (AC) alone, without the help of any catalytic species, can effectively oxidise phenol solutions without the presence of any active metal.…”
Section: ±17mentioning
confidence: 99%
“…18 Simultaneously, WAO has been extensively studied for the regeneration of AC spent with organic compounds after its use in adsorption processes. 19,20 Also, AC and other carbonaceous materials have been successfully tested as supports for catalysts, 21 even for CWAO of low molecular weight acids. 21±24 Recently, a study carried out in a trickle bed reactor has demonstrated that activated carbon (AC) alone, without the help of any catalytic species, can effectively oxidise phenol solutions without the presence of any active metal.…”
Section: ±17mentioning
confidence: 99%
“…Thus, the success in renewing the active carbon lies in minimising the surface oxidation by selecting suitable regeneration conditions. For instance, regeneration of active carbon saturated with phenol was found to be attractive only at temperatures below 1508C [27]. Anyway, phenol removal by adsorption is a discontinuous two-step process.…”
Section: Introductionmentioning
confidence: 99%
“…Annular centrifugal extractors find wide applications in nuclear fuel processing where safety is the main concern [2,8,9], in biological operations where controlled shear field and/or facilitated settling is important [10,11] and polymerization [12,13], excellent mixing, heat, and mass transfer [14][15][16][17][18][19]. Annular centrifugal extractors can also be used for a variety of chemical reactions such as synthesis of monodisperse silica particles, regeneration of spent activated carbon [20,21], esterification, and hydrolysis [22,23], as cavitation reactor [24], and they have also been demonstrated for use with ionic liquids [25].…”
Section: Introductionmentioning
confidence: 99%